f(x) = x3 + 4x2 − x − 4
f(x) = x3 + 3x2 − 4x − 12
f(x) = x3 + 2x2 − 4x − 8
Answer:
Step-by-step explanation:
From the graph, the x-intercepts are;
These are root of the polynomial function represented by the given graph.
By the remainder theorem;
According to the factor theorem, if is a factor of , then
This implies that;
are factors of the required function.
Hence;
We expand using difference of two squares to obtain;
We expand using the distributive property to get;
Rewrite in standard form to obtain;
Answer:
Choice A: f(x) = x^3 + x^2 − 4x − 4
Step-by-step explanation:
Here's a great and simple answer.
Ok first we need to take the x intercepts to solve.
If we look at the graph we see the x ints are -2,+1 and +2.
To solve we need to put them into factor form
= (x-2) (x+2) and (x+1)
Simplify: (x-2) (x+2) = (x^2-4) and (x+1)
Now we take (x^2-4) and (x+1) and multiply them to find our answer
(x^2-4) (x+1)
= x^2(x) and x^2(1) = x^3 and x^2.
now the other: -4(x) and -4(+1) = -4x and -4
We have nothing common here so we just join them
= x^3 + x^2 - 4x - 4, and that is the same as choice A.
(3/10) - (1/5) = (1/10)
Explanation:
Make sure both fractions have the same denominator. 1/5 would turn into 2/10, and 3/10 would stay the same. When the denominators are equal, subtract the numerators to get the answer.
1/5 = 2/10
(3/10) - (2/10) = (1/10)